Pines in Andhra Pradesh - Raja, K. A. Madhawa (Indian Forester, 1982)
Andhra Pradesh has been raising pine plantations since 1964. It has been observed that Pinus oocarpa is suitable for plateau region at altitudes of 1000 m or above while P. caribaea is better suited to lower altitudes. Due to shifting cuitivation and other programmes for establishment of industrial planlations the availability of area at altitudes more than 500 m is very little and plantations have to be taken in lower lands which are hot and face heat waves and are deficient in rainfall. The problems facing the programme are: Problems in importing the seed, the high price, the delays and poor quality. The total plantations are not having proper seed set, in addition the losses due to damping off, funal and by Fusarium even at a later stage, are high. The beat waves take their own toll. It is suggested that studies be taken up on (I) Control of damping off; (II) Application of mycorrhize, their isolation, selection and iaoculation; (iii) Control of Fusarium; (iv) Control of grasses and (v) Fire fighting technique.